Evaluating the Influence of Warning Labels on E-cigarette Products and Their Efficacy in Shaping User Perceptions Toward Smoking Cessation - Faisal Muttaqin; Romi Adetio Setiawan; Evan Stiawan; John Kenedi; Rohmadi (International Journal of Preventive Medicine)
Background: The effectiveness of warning labels on tobacco products in conveying health risks and promoting smoking cessation has been extensively studied. However, with the rise in electronic cigarette (E-cigarette) usage, there is a need to assess the impact of warning labels specifically tailored to this emerging market. This study aims to fill this gap by examining the effectiveness of warning labels on E-cigarette packaging in influencing smokers’ perceptions and intentions to quit. Method: A laboratory experiment was conducted, involving 180 participants comprising both conventional smokers and E-cigarette users. There are three experimental designs used in this research, which are subjected to conventional smokers and E-cigarette smokers. Participants were randomly located within each of the six cells. Each cell was given a different stimulus. Results: The study revealed that warning labels on E-cigarette products significantly influenced participants’ perceptions and intentions to quit smoking. Specifically, E-cigarette users perceived packaging with warning labels differently from those without. Moreover, visual warning labels were found to be more effective than textual ones in eliciting perceptions and intentions to quit smoking. Conclusions: These findings underscore the importance of warning labels in conveying health risks and promoting smoking cessation intentions among E-cigarette users, offering valuable insights for public health strategies.